The Implementation of Differentiated Instruction and Its Impact on the Teaching Stress Levels of Islamic Education (PAI) Teachers at SMAN 2 Situbondo - Alwi, Wildan; Khadijah, Khadijah; Furqon, Muhammad; Mukhtar, Muhammad Kamil; Marhamah, Marhamah (UMSU, 2025)
This study aims to examine the practice of differentiated learning carried out by Islamic Education (PAI) teachers at SMAN 2 Situbondo and to identify the obstacles encountered during its implementation. The research employed a qualitative approach with a field research design. Data were obtained through observation, interviews, and documentation, while the validity of the data was ensured by applying source and technique triangulation, supported by reference materials and member checking. The process of data analysis involved stages of collection, reduction, presentation, and conclusion drawing. The findings reveal that differentiated learning strategies covering content, process, and product have been applied in classroom instruction, yet challenges persist, particularly regarding teachers’ limitations in adapting strategies to the diverse needs of students. The study concludes that enhancing teachers’ competence in differentiated instruction is essential to minimize teaching stress and improve the overall effectiveness of the learning process.